Development of Simple Analytical Method to Determine Amlodipine in Rat Plasma A Preclinical Study Applicable To Bioequivalence Test - Bijay Aryal, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Development of Simple Analytical Method to Determine Amlodipine in Rat Plasma A Preclinical Study Applicable To Bioequivalence Test